A joint electromagnetic and seismic study of an active pockmark within the hydrate stability field at the Vestnesa Ridge, West Svalbard margin - Goswami, Bedanta K.; Weitemeyer, Karen A.; Minshull, Timothy A.; Sinha, Martin C.; Westbrook, Graham; Chabert, Anne; Henstock, Timothy J.; Ker, Stephan (Journal of Geophysical Research: Solid Earth, 2015)
We acquired coincident marine controlled-source electromagnetic (CSEM), high-resolution seismic reflection and ocean-bottom seismometer (OBS) data over an active pockmark in the crest of the southern part of the Vestnesa Ridge, to estimate fluid composition within an underlying fluid-migration chimney. Synthetic model studies suggest resistivity obtained from CSEM data can resolve gas or hydrate saturation greater than 5% within the chimney. Acoustic chimneys imaged by seismic reflection data beneath the pockmark and on the ridge flanks, were found to be associated with high-resistivity anomalies (+2-4 m). High-velocity anomalies (+0.3 km/s), within the gas hydrate stability zone (GHSZ) and low-velocity anomalies (-0.2 km/s) underlying the GHSZ, were also observed. Joint analysis of the resistivity and velocity anomaly indicates pore saturation of up to 52% hydrate with 28% free gas, or up to 73% hydrate with 4% free gas, within the chimney beneath the pockmark assuming a non-uniform and uniform fluid distribution respectively. Similarly, we estimate up to 30% hydrate with 4% free gas or 30% hydrate with 2% free gas within the pore space of the GHSZ outside the central chimney assuming a non-uniform and uniform fluid distribution respectively. High levels of free-gas saturation in the top part of the chimney are consistent with episodic gas venting from the pockmark.